Functional characterization of novel compound heterozygous missense SLC5A5 gene variants causing congenital dyshormonogenic hypothyroidism - Carro, Gerardo Hernán; Martín, Mariano; Savy, Sofía; Peyret, Victoria; Geysels, Romina Celeste; Montes, Francisco Andrés; Bernal Barquero, Carlos Eduardo; Ricci, Valentina; Masnata, María Eugenia; Masini-Repiso, Ana María; Papendieck, Patricia; Tellechea, Mariana Lorena; et al. (Frontiers in Endocrinology, 2024)
The sodium/iodide symporter (NIS) mediates active iodide accumulation in the thyroid follicular cell. Biallelic loss-of-function variants in the NIS-coding SLC5A5 gene cause congenital dyshormonogenic hypothyroidism due to a defect in the accumulation of iodide, which is required for thyroid hormonogenesis. Here, we aimed to identify, and if so to functionally characterize, novel pathogenic SLC5A5 gene variants in a patient diagnosed with severe congenital dyshormonogenic hypothyroidism characterized by undetectable radioiodide accumulation in a eutopic thyroid gland, as well as in the salivary glands. Proposita's wholeexome sequencing revealed a novel pair of compound heterozygous missense variants in the SLC5A5 gene, c.1,627G>A (p.G543R) and c.1,684T>A (p.L562M). The parents were heterozygous carriers of the variants as determined by Sanger sequencing of the SLC5A5 gene.The p.G543R variant in the homozygous state has previously been associated with congenital hypothyroidism. The novel p.L562M variant was not reported in the Genome Aggregation Consortium dataset. In silico analysis of the pathogenic impact of the p.L562M variant yielded inconclusive results. Functional in vitro studies showed that the p.L562M variant reduces iodide accumulation due to defective expression of the mutant NIS protein at the plasma membrane.Notably, the aliphatic residue Leu at position 562 in the carboxy terminus of the protein, which is highly conserved in NIS orthologues, is required for NIS plasma membrane expression. In conclusion, we report novel compound heterozygous missense SLC5A5 gene variants causing defective iodide accumulation, thus leading to congenital dyshormonogenic hypothyroidism.